Microbial nitrogen bubble formation in porous media - Kim, Daehyun; Kang, Hojeong; van Paassen, Leon A.; Wang, Liya; Yun, Tae Sup; Hata, Toshiro (Heliyon, 2024)
Microbially induced nitrogen (N2) gas bubbles can desaturate subsurface areas and thus have been considered as an alternative ground improvement technique for mitigating soil liquefaction potential caused by earthquakes. However, the detailed mechanisms of subsurface N2 bubbles are not well understood and remain a subject of ongoing research. In this study, a transparent microfluidic device was utilized to mimic biological N2 gas bubble formation by nitrate-reducing bacteria and to visually characterize the entire process. During N2 gas formation, a limited number of bubble nucleation sites were identified, which gradually expanded upward through the preferential pore channels. N2 gas bubbles tended to create interconnected gas pockets rather than existing as evenly distributed small gas cavities. The degree of water saturation gradually reduced over a week as the bubbles were produced. The gas ganglia repeatedly grew until they reached the top boundary, which triggered a drastic expulsion of bubbles by ebullition. Despite fluctuations in saturation level, the residual saturation was maintained at around 73 %. Comparative experimental case studies of CO2 gas bubble formation were conducted to identify contrasting gas formation mechanisms. CO2 gas bubbles were generated via the abiotic decompression of a supersaturated CO2 solution under two distinct rates of pressure reduction. Rapid CO2 bubble formation led to uniform nucleation and 41 % residual saturation, while slower formation yielded 35 % due to stable liquid displacement by the gas front. This study highlights the potential of the microfluidic device as an experimental tool for visualizing subsurface gas formation mechanisms. The insights gained could further enhance and optimize geotechnical applications involving gas formation in highly saturated soils. •Microfluidic tests reveal subsurface microbial N2 bubble formation mechanisms.•Bubble formation mechanisms and saturation levels vary with gas type and formation rate.•Biogenic N2 bubble formation favors bubble growth; rapid CO2 disperses more evenly.•The implications and necessary cautions when using microfluidic devices are discussed.